Water vapor transport in cases of South Atlantic Convergence Zone (SACZ) (Research, Society and Development, 2021)
This case study analyzes water vapor flux that is vertically integrated into the atmosphere in episodes of the South Atlantic Convergence Zone (SACZ). The scope of this study is two cases that occurred between January and February 2018. We use the ERA-Interim reanalysis data from the European Center for Medium-Range Weather Forecasts (ECMWF) to build the maps of vertically integrated water vapor flux and its divergence. We use two 5º by 5º sub-areas, centralized over Belo Horizonte and São Paulo, as control for water vapor balance. The results point to the existence of water vapor transport from the Amazon region to Southeastern Brazil in association to the SACZ. Convergence areas of vertically integrated water vapor flux predominate along the Northwest-Southeast line. The two cases over the Belo Horizonte area presented an average of water vapor balance of -1.8 and -12.9 mm/day. The average at the São Paulo area was -3.6 and 2.0 mm/day. The negative values indicate that precipitation exceeded evapotranspiration, that is, the area served as a water vapor sink.